In Vitro Activity of Omadacycline and Comparator Antibiotics against Extended-Spectrum Beta-Lactamase-Producing Escherichia coli and Klebsiella pneumoniae Urinary Isolates - Tyler J. Stone; Abdullah Kilic; John C. Williamson; Elizabeth L. Palavecino (MDPI AG, 2023)
Limited oral antibiotic options exist for urinary tract infections (UTI) caused by ESBL-producing Enterobacterales. The aim of the study was to evaluate in vitro activity of omadacycline and comparator antibiotics against clinical ESBL-producing and non-ESBL-producing E. coli and K. pneumoniae urinary isolates. 102 isolates each of E. coli and K. pneumoniae were collected from clinical urine specimens in 2019. By design, an equal number of each species were included that tested positive and negative for ESBL production. Omadacycline MICs were determined using gradient test strips and compared to MICs of comparator antibiotics as determined by an automated broth microdilution system. Isolates were considered susceptible to omadacycline if the MIC was ≤4 µg/mL for each species. 54.9% of all ESBL-producing isolates were susceptible to omadacycline, but better susceptibility was observed for ESBL-producing E. coli (74.5%). Omadacycline MICs were 2-4 fold lower for E. coli and K. pneumoniae strains not producing ESBL. The omadacycline MIC 50 and 90 values were 4 and 16 µg/mL, respectively, for all isolates studied. 74.5% of all isolates were considered susceptible to omadacycline. MICs were generally lower for E. coli strains with MIC 50 and 90 values of 4 and 8 µg/mL, respectively (87.3% susceptible), compared with K. pneumoniae. Overall, the most active agents were omadacycline and nitrofurantoin, while other comparator antibiotics were less active. Omadacycline represents a promising oral antibiotic for treating UTI caused by ESBL-producing E. coli, particularly when resistance limits other oral options. Prospective, controlled clinical trials are needed to validate these in vitro results.